2016
DOI: 10.5713/ajas.15.0270
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Analysis of the Genetic Diversity and Population Structure in Dairy Goats in Thailand

Abstract: The genetic relationships between different populations and breeds of exotic dairy goats in Thailand were studied using 12 microsatellite markers. Blood samples were obtained from 211 goats from Department of Livestock Development breeding and research farms: 29 Anglonubian (AN), 21 Alpine (AP), 23 Jamunapari (JAM), 50 Saanen (SN), and 88 Toggenburg (TG). Five of the 12 microsatellite markers were found to be polymorphic. A mean of 7.40 alleles per locus was found, with a range from 5 (SPS115 and ETH225) to 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
6
1
1
Order By: Relevance
“…The observed numbers of alleles in this study were consistent with numbers of alleles observed by Nahashon et al (2008);Agung et al (2016) and Seilsuth et al (2016) when microsatellite markers were used with common animal genetic resources. Considering allele numbers range limits in this study, it means that the lower limit was greater than 4, the minimum number of alleles suggested by Wimmers et al (2000) and FAO (2004; for microsatellite markers to be used with any genetic resource.…”
Section: Resultssupporting
confidence: 92%
“…The observed numbers of alleles in this study were consistent with numbers of alleles observed by Nahashon et al (2008);Agung et al (2016) and Seilsuth et al (2016) when microsatellite markers were used with common animal genetic resources. Considering allele numbers range limits in this study, it means that the lower limit was greater than 4, the minimum number of alleles suggested by Wimmers et al (2000) and FAO (2004; for microsatellite markers to be used with any genetic resource.…”
Section: Resultssupporting
confidence: 92%
“…In a Thai dairy goat study on genetic diversity, five imported breeds (Alpine, Jamunapari, Nubian, Saanen, and Toggenburg) were evaluated using five microsatellite markers [45]. A mean of 7.4 alleles per population per marker was found, F IS values ranged between 0.18 and −0.04, and F ST was 0.07.…”
Section: Genomicsmentioning
confidence: 99%
“…Most of the milk produced by the goats is either fed to kids by the does or generally home-consumed, given to the neighborhood or sold within the villages themselves. Dairy goats are supporting millions of malnourished human population in the developing world [7]. Goat milk has also been found to be useful for the patients of diabetes, peptic ulcers, allergy and various gastrointestinal disorders [4].…”
Section: Introductionmentioning
confidence: 99%